Rare Case of Four Osseous Lesions of the Skull in a Patient with Secondary Syphilis - Jace Kusler; Supha Arthurs (Case Reports in Infectious Diseases)
Syphilis is a sexually transmitted infection that is caused by the bacterium Treponema pallidum. Syphilis can present as primary, secondary, tertiary, or congenital. It can have an effect on many different organ systems and tissues leading to a wide variety of symptoms and complications; one rare manifestation is bone involvement. The patient in this case was diagnosed with secondary and early neurosyphilis and was also found to have skull lesions that were due to Treponema pallidum. There are guidelines for the treatment of primary, secondary, tertiary, and congenital syphilis; however, there are currently no guidelines for the treatment of syphilis with bone involvement.